2004
DOI: 10.1080/00087114.2004.10589392
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organizer regions as markers of chromosomal polymorphism in Apareiodon affinis (Pisces, Parodontidae)

Abstract: -Specimens of Apareiodon affinis collected from four sites of the Paraná River (called Lower Paraná, Argentina) were analyzed. This species presents a diploid number of 54 chromosomes, without any apparent sex chromosomal heteromorphism. However, it was possible to verify the occurrence of 10 cytotypes, some of them common to all collected sites, characterizing an structural chromosomal polymorphism. Data obtained from chromosomal banding methods, results further suggest an inter-individual NOR polymorphism. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(9 reference statements)
1
14
0
Order By: Relevance
“…chromosomes has a pattern similar to those observed in the karyotypes of other parodontids, as well as the conspicuous heterochromatic block in the longer arm of the W chromosome in those species with a ZZ/ZW sex chromosome system , 1993Jesus et al, 1999;Jesus and Moreira-Filho, 2000a, b;Centofante et al, 2002;Vicente et al, 2003;Jorge and Moreira-Filho, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…chromosomes has a pattern similar to those observed in the karyotypes of other parodontids, as well as the conspicuous heterochromatic block in the longer arm of the W chromosome in those species with a ZZ/ZW sex chromosome system , 1993Jesus et al, 1999;Jesus and Moreira-Filho, 2000a, b;Centofante et al, 2002;Vicente et al, 2003;Jorge and Moreira-Filho, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…A pericentric inversion concerning the first karyotypic pair was detected in Serrasalmus spilopleura (Serrasalminae) from the Catalão Lake (Amazon basin), with absence of the structural homozygotes (Centofante et al, 2002). Variations concerning the number of the acrocentric chromosomes in Apareiodon affinis (Parodontidae) from the lower Paraná River (Argentina) were also probably due to pericentric inversions, since the diploid number (2n = 54) was constant in the population (Jorge & Moreira-Filho, 2004). Pericentric inversions were also considered in order to explain another few cases of structural polymorphisms, as in Hoplerythrinus unitaeniatus (Erythrinidae) from the Negro River, in the Amazon basin (Giuliano-Caetano & Bertollo, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, these variations have been confirmed by the use of fluorescent in situ hybridization (FISH) with 18S rDNA probes (Kavalco et al, 2005;Mantovani et al, 2005;Pazza et al, 2006). However, structural polymorphisms due to other chromosomal rearrangements such as inversions and centric fusions/ fissions are not very common among Neotropical fish, being known mainly among Characiformes (Giuliano-Caetano & Bertollo, 1988;Cestari & Galetti Jr.,1992;Centofante et al, 2002;Jorge & Moreira Filho, 2004;Pazza et al, 2006). In Siluriformes, numerical and/or structural polymorphisms were observed in a few Pimelodidade (Dias & Foresti, 1993;Vasconcelos & Martins-Santos, 2000), Heptapteridae (Vissoto et al, 2001;Kavalco et al, 2004), Hypoptopomatinae (Andreata et al, 1994), Loricariinae (Giuliano-Caetano, 1998), and Trichomycteridae species (Borin & Martins-Santos, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…3). Chromosome rearrangements due to inversions have been described in some fish groups (Centofante et al, 2002;Jorge & Moreira-Filho, 2004), with some cases involving the NORbearing chromosomes (Porto-Foresti et al, 2004;Mariotto et al, 2009). Based on experimental crosses of farmed stocks of the salmonid Oncorhynchus mykiss, Porto-Foresti et al (2004) suggested that a particular combination of chromosomes with inversions might be lethal in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%